Challenges of continued training: a reading of the spaces of continued training from the teachers of history of the state public school network - Chagas, Varli Lucidônio das (Revista Hipótese, 2018)
This article has as objective to analyze the continuous formation from the teachers of History that work in the public network of Santa Catarina. The education occupation are in a very important area, they build opinions, they are undeniable in their strong performance in society, in the face of this scenario they need to be prepared for the technological and competitive challenges, and they will find many obstacles in the way. The education occupation often teaches in many schools and with a broad workload, it is up to here an analysis whether public school managers for continuing training for professionals. The research questionnaires answered by History teachers of the state network of Santa Catarina, it was realized that as training for an area of basic education and small issues in pedagogies, and when they occur in a short time, usually no beginning and middle of the school year has been no much expressive for an educator's training.
Keywords: Teacher; History; Continued Formation